THE EFFECT OF MOBILE LEARNING-BASED TEAM GAME TOURNAMENT LEARNING MODEL ON RECOUNT TEXT WRITING ABILITY: THE ROLE OF LEARNING STYLE AS VARIABLE MODERATION - Purwo Haryono; Tukiyo Tukiyo (University of Kuningan, 2022)
The aim of this study is to use quantitative research methods and causality models to investigate the proposed hypothesis of the mobile learning-based team game tournament learning model effect on the recount text writing ability: The Role of Learning Style as a Moderating Variable. The participants in this study are pupils from Kartasura's Al-Islam Junior High School. This study's sample consisted of 100 students chosen using a basic random selection procedure. SEM (Structural Equation Modeling) is the analytical technique employed, and it is controlled by Smart PLS application. The results show that the Team Game Tournament learning model had a substantial beneficial effect on the capacity to write recount text, and the learning style had a significant positive influence on the students' ability to write recount text. In addition, to improve the learning model for the team game tournament's recount text writing abilities, it's important to consider the learning style of each participant.